Informed Consent in Surgical Patients Current Issues and Future Perspective - Umm-E-Habiba Abdul Rauf, Mujeeb Rehman Malik, Faisal Ghani Siddiqui, Omema Saleem, Summaya Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Informed consent is an essential and standard procedure in medical practice. The objective of the study was to evaluate the informed consent practices of surgeons at a university teaching hospital. Materials and Methods: A prospective cross sectional study was performed between the time duration of February 2022 till June 2022 at surgical and allied units of Dow University Hospital, DUHS Karachi, Pakistan Results: A total of 196 patients were interviewed on their first post-operative day at their bed side. . Patients were selected randomly from all surgical and allied departments of Dow university hospital, including Gynecology(36.22%), General surgery(34.18%), orthopedics(16.33%), ENT (6.12%), urology (2.55%), eye (2.55%), neurosurgery(1.53%) and maxillofacial(0.51%). 39.8% patients gave consent themselves while rest 55.1% and 5.1% consents were given by family members and parents. Only 23.47% patients or the representative who signed the consent, read the consent form before signing it Conclusions: To improve the quality of communication with the informed consent, a structured conversation helps physicians establish relationships with the patients, regarding the adequacy of the information provided. Keywords: Surgical Patients, informed consent, communication